Transmembrane glycoprotein gp41 of the Human Immunodeficiency Virus Type I : gene synthesis, recombinant expression and immunological characterization - Verschoor, Jan Adrianus (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.